Food, Financial Crises, and Complex Derivatives : A Tale of High Stakes Innovation and Diversification - Songwe, Vera (World Bank, Washington, DC, 2012)
The 2008 food price crisis was an integral part of the financial crisis. In fact, the food price crisis was the second crisis in a chain of events that began in 2007 with the mortgage crisis, and culminated in the worst financial crisis since the Great Depression. Contrary to what was generally believed in 2008, developing countries, particularly food-importing countries, were part of the early wave of the financial crisis via food price increases, and later suffered another wave via the real sector. The events leading up to the food crisis were global and complex in nature. As a result, as the G-20 discusses solutions to the financial crisis, any new framework must include developing countries, especially low-income countries. In addition, developing countries, especially in Africa, must pay close attention to the work of the Financial Stability Board (FSB) and its recommendations on financial market reform, and over-the-counter (OTC) derivatives in particular, because these reforms will have important consequences for their housing, food, fuel, financial markets, and ultimately their growth and poverty reduction objectives.